In vitro activity of aryl-thiazole derivatives against Schistosoma mansoni schistosomula and adult worms - Pereira, Adriana S. A. (PLoS One, 2019)
Schistosomiasis is caused by a trematode of the genus Schistosoma and affects over 200 million people worldwide. The only drug recommended by the World Health Organization for treatment and control of schistosomiasis is praziquantel. Development of new drugs is therefore of great importance. Thiazoles are regarded as privileged structures with a broad spectrum of activities and are potential sources of new drug prototypes, since they can act through interactions with DNA and inhibition of DNA synthesis. In this context, we report the synthesis of a series of thiazole derivatives and their in vitro schistosomicidal activity by testing eight molecules (NJ03-08; NJ11-12) containing thiazole structures. Parameters such as motility and mortality, egg laying, pairing and parasite viability by ATP quantification, which were influenced by these compounds, were evaluated during the assays. Scanning electron microscopy (SEM) was utilized for evaluation of morphological changes in the tegument. Schistosomula and adult worms were treated in vitro with different concentrations (6.25 to 50 μM) of the thiazoles for up to 5 and 3 days, respectively. After in vitro treatment for five days with 6.25 μM NJ05 or NJ07 separately, we observed a decrease of 30% in schistosomula viability, whilst treatment with NJ05+NJ07 lead to a reduction of 75% in viability measured by ATP quantitation and propidium iodide labeling. Adult worms’ treatment with 50 μM NJ05, NJ07 or NJ05 + NJ07 showed decreased motility to 30–50% compared with controls. Compound NJ05 was more effective than NJ07, and adult worm viability after three days was reduced to 25% in parasites treated with 50 μM NJ05, compared with a viability reduction to 40% with 50 μM NJ07. SEM analysis showed severe alterations in adult worms with formation of bulges and blisters throughout the dorsal region of parasites treated with NJ05 or NJ07. Oviposition was extremely affected by treatment with the NJ series compounds; at concentrations of 25 μM and 50 μM, oviposition reached almost zero with NJ05, NJ07 or NJ05 + NJ07 already at day one. Tested genes involved in egg biosynthesis were all confirmed by qPCR as downregulated in females treated with 25 μM NJ05 for 2 days, with a significant reduction in expression of p14, Tyrosinase 2, p48 and fs800. NJ05, NJ07 or NJ05+NJ07 treatment of HEK293 (human embryonic cell line) and HES (human epithelial cell line) showed EC50 in the range of 18.42 to 145.20 μM. Overall, our results demonstrate that those molecules are suitable targets for further development into new drugs for schistosomiasis treatment, although progress is needed to lessen the cytotoxic effects on human cells. According to the present study, thiazole derivatives have schistosomicidal activities and may be part of a possible new arsenal of compounds against schistosomiasis.